IMPACT OF MOTIVATIONAL FACTOR ON PERFORMANCE OF INDUSTRY, TRADE, COOPERATIVE, AND SME SERVICE EMPLOYEES IN LANGSA CITY - Zati, Muhammad Rizqi; Rosalina, Dhian; Renita, Renita (Jurnal Apresiasi Ekonomi, 2024)
The purpose of this study was to determine the effect of motivational factors consisting of transformational leadership, work motivation, and career development on employee performance at the Department of Industry, Trade, Cooperatives, and Small and Medium Enterprises in Langsa City. The census technique was used in this study, with the research respondents totaling fifty-five respondents with State Civil Apparatus status, with leaders excluded from the sample. The data analysis method used in this study is a multiple linear regression equation. The results of this study indicate that transformational leadership has no significant effect on performance. Work motivation has a positive and significant effect on employee performance, and HR development significantly affects performance.Keywords: Transformational leadership. Work motivation, career development, and performance